Energy Efficient Selection of Cluster Headers in Wireless Sensor Network - Adem Fanos Jemal (The Graduate School, Ajou University, 2014)
Energy efficient cluster head placement mechanism is vital for elongating the lifespan of resource-constrained wireless sensor nodes. In this research work we used energy efficient Cluster head placement algorithm and we proposed fault tolerant Cluster head selection algorithm. The performance of the proposed scheme is evaluated for energy consumption, end to end (E2E) delay as well as packet loss. The evaluation is carried out by using OPNET simulation tool. Our simulation result reveals that the energy consumption of our proposed scheme is better than the LEACH mechanism. The higher energy consumption of the LEACH scheme may be resulted from the communication overhead incurred during cluster head setup process. End-to-end delay performance of our scheme is also better than that of the LEACH mechanism. Key words: WSN, Cluster Head, LEACH, Gateway
학위논문(석사)--아주대학교 일반대학원 :컴퓨터공학과,2014. 8